Role of 5HT1A Receptors in the Neuroprotective and Behavioral Effects of Cannabidiol in Hypoxic–Ischemic Newborn Piglets - Barata, Lorena; de Hoz-Rivera, María; Romero, Angela; Martínez, María; Silva, Laura; Villa, María; Campa, Leticia; Jiménez-Sánchez, Laura; Martínez-Orgado, José (Frontiers in Pharmacology, 2022)
Background: hypoxic-ischemic (HI) insults have important deleterious consequences in newborns, including short-term morbidity with neuromotor and cognitive disturbances. Cannabidiol (CBD) has demonstrated robust neuroprotective effects and shows anxiolytic/antidepressant effects as well. Those effects are thought to be related with serotonin 5-HT1A receptor (5HT1AR) activation. We hereby aimed to study the role of 5HT1AR in neuroprotective and behavioral effects of CBD in HI newborn piglets. Methods: HI 1-day-old piglets were treated daily with vehicle, CBD 1 mg/kg or CBD with the 5HT1AR antagonist WAY 100635 1 mg/kg. 72 h post-HI piglets were studied using amplitude-integrated EEG to detect seizures and a neurobehavioral test to detect neuromotor impairments. In addition, behavioral performance including social interaction, playful activity, hyperlocomotion and motionless periods were assessed. Then, brain damage was assessed using histologic (Nissl and TUNEL staining) and biochemistry (proton magnetic resonance spectroscopy studies. Results: HI led to brain damage as assessed by histologic and biochemistry studies, associated with neuromotor impairment and increased seizures. Those effects were not observed in HI piglets treated with CBD. These beneficial effects of CBD were not reversed by the 5HT1AR antagonist, which is on contrast with previous studies demonstrating that 5HT1AR antagonists eliminated CBD neuroprotection as assessed 6 h after HI in piglets. HI led to mood disturbances, with decreased social interaction and playfulness and increased hyperlocomotion. Mood disturbances were not observed in piglets treated with CBD, but in this case coadministration of the 5HT1AR antagonist eliminates the beneficial effects of CBD. Conclusions: CBD prevented HI-induced mood disturbances in newborn piglets by acting on 5HT1AR. However, 5HT1AR activation seems to be necessary for CBD neuroprotection only in the first hours after HI.